Estudo de caso: resistência de compressão diametral de tubos de concreto de 40 cm de diâmetro com e sem armação - Cruz, Fernando Henrique Mattiello (2019)
Circular section concrete pipes are widely used in sanitation constructions in Brazil, mainly for rainwater and sewage conduction, and they can be produced in simple or reinforced concrete. Because of this, there is a need to carry out studies to evaluate their resistance and ability to withstand the pressures generated by the surrounding soil. Moreover, it is necessary to assess if they are complying with regulatory requirements and if they meet the quality expected by the market. This research measures the conformity and diametral compressive strength of reinforced and non-reinforced concrete pipes, with a nominal diameter of 400 mm with male and female fitting, in relation to normative requirements, including analysis of the production process and aggregates used in dry concrete production, for two different mixing ratios. The results demonstrated that the presence of welded screen reinforcement in the evaluated tubes significantly increased the resistance to diametral compressive strength, even though it was used a mix proportion with lower axial compressive strength. It can also be concluded that, in general, the pipes comply with the regulatory requirements.